Research on IP Innovation and Communication Strategies of Intangible Cultural Heritage in Tai’an City in the Digital Consumption Era - Li, Yang (International Journal of Social Sciences and Public Administration, 2025)
In the new era, revitalizing the dissemination and promotion of intangible cultural heritage and increasing its audience is the key to its survival. Innovating the IPization of intangible cultural heritage makes it easier to capture the fleeting attention of audiences in a society with excessive dissemination. Spreading intangible cultural heritage through various online and offline channels such as "intangible cultural heritage IP + content", "intangible cultural heritage IP + tourism", "intangible cultural heritage IP + cultural and creative products", and "intangible cultural heritage IP + finance", and constructing a full media communication matrix can help build a fan circle for intangible cultural heritage, expand its application value and economic value, effectively improve its self-generating ability, and promote the sustainable inheritance and dissemination of intangible cultural heritage.